Fifty Applications of the CMOS Inverter-Part 4 [The Analog Mind] - Razavi, Behzad (IEEE solid state circuits magazine, 2025)
In this article series, we have studied the use of the CMOS inverter in various analog and digital systems. As mentioned in the previous installments, the low supply voltages imposed by modern CMOS processes have made the inverter attractive for realizing circuit functions. In this article, we examine more topologies and quantify their performance in the slow-slow corner of 28-nm technology with V DD = 95 V and at T = 75 °C.